Mining the Species Diversity of Lacewings: New Species of the Pleasing Lacewing Genus Dilar Rambur, 1838 (Neuroptera, Dilaridae) from the Oriental Region - Di Li; Horst Aspöck; Ulrike Aspöck; Xingyue Liu (Insects, 2021)
The species diversity of insects is extraordinarily rich, but still has been insufficiently explored or underestimated particularly for uncommon groups. The pleasing lacewings (Dilaridae) are a little known family of Neuroptera with distinct sexually dimorphic antennae. The species diversity of pleasing lacewings was recently found to be severely underestimated and requires a comprehensive investigation, as well as systematic reviews. Here, we report on 12 new species of the pleasing lacewing genus Dilar Rambur, 1838, from the Oriental region, namely D. forcipatus sp. nov. and D. laoticus sp. nov. from Laos (new country record of Dilar); D. malickyi sp. nov., D. phraenus sp. nov. and D. rauschorum sp. nov. from northern Thailand; D. striatus sp. nov. from northern Vietnam; D. cangyuanensis sp. nov., D. daweishanensis sp. nov., D. nujianganus sp. nov., D. weibaoshanensis sp. nov., D. yucheni sp. nov., and D. zhangweiae sp. nov. from Yunnan and Tibet, both in southwestern China. The new species of Dilar display several types of wing marking patterns, and the morphology of the male genitalia is highly diverse. A comprehensive examination of the species diversity and distribution of Dilar concluded that Yunnan (southwestern China) represents a biogeographic region with high endemism and the richest species diversity. The potential correlation between vertical distribution and geographical latitude in Dilar was also analyzed.